Semeadura da soja em sistemas de rotação de culturas e integração agricultura-pecuária em um latossolo sob sistema de plantio direto - Gurgacz, Flavio (2007)
The no tillage system with cattle-raising integration blunts as an alternative to agricultural activities diversification providing income increase, production risks decrease and optimization of the machinery and inputs. The no tillage seed drill available in the market disposal some components that adapts itselves to different plantation conditions. On the other hand some information are necessary to indicate in which situations the mechanism must be modified and what is its effect in the culture implantion. In this direction it was conducted a research under an oxisol in Cascavel-PR evaluating the performance of a fertilizer and seed drill in the implantation of soybean culture under different systems of soil management. Were used fertilizer coulters cinzel type, double disc and its absence under two rotation systems (wheat/soybean and covering plant/soybean) and cattle-raising integration. For the area characterization were determined the density, macroporosity, microporosity, penetration resistance, humidity and soil vegetal covering. In the tractor were determined the fuel consumption, the drawbar force, pneumatic slip, rotation of the engine and speed. The other evaluated parameters were the depth of ridge and seeds, mobilized soil in the line, index of emergency speed (IVE), plant population and productivity. The results showed a tendency of modification in the soil physics parameters according to management system and a modification in the seeder performance equipped with different coulters under the different soil conditions.The fuel consumption, drawbar force, pneumatic silp and speed were significantly modified by the coulter mechanism. The cinzel coulter showed greater depth of ridge and seeds, soil mobilizing in the line and minor IVE. The soybean productivity was not influenced by the coulter mechanism but was affected by the management system being the major value obtained in the cattle-raising integration system in function of the biggest population of plants gotten. It was concluded that when it works with different management systems it is necessary to modify the coulters of soil preparation in the sowing line to get the desired results.